Biotransformation of salicylaldehyde to salicin using Varthemiapersicacell suspension cultures: Biotransformation of salicylaldehyde - Gholamreza Asghari; Maryam Mosaeybi (Iranian Journal of Pharmaceutical Sciences, 2009)
Cell cultures of Varthemia persicaDC. have been studied to evaluate their abilities in biotransformation of aromatic and aliphatic precursors. V. Persica (Asteraceae) is an aromatic plant growing in Iran. V. persicacontain different terpens but its cell culture does not posses these compounds. Callus cultures of V.persicawas established from seedlings and healthy suspensions were grown using Murashige and Skoog (MS) medium supplemented with 2,4-dichlorophenoxy acetic acid (2 mg/l) and kinetin (0.2 mg/l). Then exogenous precursors were fed toV. persicacell suspension cultures. Biotransformation reactions were monitored after 24 h of incubation. The cultures then extracted with dichloromethane or methanoland concentrated within nitrogen stream. The extracts subjected to gaschromatography (GC) or thin layer chromatography (TLC) analysis. V. persicacultured cells in this study seem to exhibit ability in glucosylation of salicylalde-hyde to salicin. No conversion was observed with several precursors fed to the cultures. The ability of cultured plant cells in biotransformation of the precursors appears to be depending on the substrate structure and active enzymes available in the cultures. It seems that in cultured cells of this plant only glucosylation enzymes are active.